If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + 7 = 5 + 37 Reorder the terms: 7 + 11x = 5 + 37 Combine like terms: 5 + 37 = 42 7 + 11x = 42 Solving 7 + 11x = 42 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 11x = 42 + -7 Combine like terms: 7 + -7 = 0 0 + 11x = 42 + -7 11x = 42 + -7 Combine like terms: 42 + -7 = 35 11x = 35 Divide each side by '11'. x = 3.181818182 Simplifying x = 3.181818182
| x^2-8x-11=0 | | 5x-18=32 | | 1-1+1-1= | | 4(4c-1)-3=11c+3 | | t^2=-35-12t | | 7x+1/7=8x+5/7 | | 201=3(3-8n) | | 24x+6-26x=2-6 | | k^2+12k+36=0 | | 75-2x=3x+5 | | 82+6y-32=17y-13-2y | | 353425-43x=24+1245422x | | -6-2x=12.8x | | x^2+6x+34=0 | | 165-3x=24x+21 | | -4/-4= | | -3x^6-6x^5+45x^4= | | 5-9x=46-16x | | 6/2=x | | 15-4n=19 | | 3(x+16)= | | 8x-18=5+4x | | 2(3y-x)= | | 224-5x=31x+16 | | 12xy-18x+6-8y=0 | | 17p+4p^2=-15 | | 8x-20+3x=35 | | 7x-47=4x-14 | | 5x+3=5+4x | | 126-4x=6x+6 | | -3y-37=6y+17 | | 5x+6+2x=48 |